The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/ijfs.15407
|View full text |Cite
|
Sign up to set email alerts
|

Potential applications and limitations of edible coatings for maintaining tomato quality and shelf life

Abstract: Tomato is among the most commercialised fruits due to its high nutritional value and health-promoting compounds. However, tomatoes have a short shelf life and plastic packaging materials are used to mitigate perishability. Nevertheless, the exhaustion of nonrenewable natural resources used to produce plastics and demand for eco-friendly packaging entailed search for other alternatives. Edible coatings have emerged as an effective and environmentally friendly alternative to protect fruits from physical and chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 92 publications
2
29
0
1
Order By: Relevance
“…But those reports are with bit complex preparation steps and with ingredients like beeswax. Our approach is simple, devoid of wax materials and the results of this study are better in terms of weight loss and firmness control than the reported findings for tomatoes (Duguma, 2022; N. Kumar et al, 2021; Ruelas‐Chacon et al, 2017). In particular, this study displayed results with extended shelf life up to ~21 days without any cracks under ambient conditions (temperature ~25°C with RH 70%).…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…But those reports are with bit complex preparation steps and with ingredients like beeswax. Our approach is simple, devoid of wax materials and the results of this study are better in terms of weight loss and firmness control than the reported findings for tomatoes (Duguma, 2022; N. Kumar et al, 2021; Ruelas‐Chacon et al, 2017). In particular, this study displayed results with extended shelf life up to ~21 days without any cracks under ambient conditions (temperature ~25°C with RH 70%).…”
Section: Resultsmentioning
confidence: 55%
“…But those reports are with bit complex preparation steps and with ingredients like beeswax. Our approach is simple, devoid of wax materials and the results of this study are better in terms of weight loss and firmness control than the reported findings for tomatoes (Duguma, 2022;N. Kumar et al, 2021;Ruelas-Chacon et al, 2017).…”
Section: Weight Loss and Firmnessmentioning
confidence: 57%
“…In the case of ripe tomatoes, these changes occur more quickly, leading to spoilage. The main processes involved in weight loss are the evaporation of water and respiration [21,28]. Therefore, the natural weight loss of the fruit is a crucial factor in determining its quality during storage [28].…”
Section: Tomato Preservation Using Composite Biofilm Chitosan-mccmentioning
confidence: 99%
“…Other issues related to the efficacy of edible films/coatings include their poor moisture-barrier properties due to the hydrophobic nature of the majority of edible packaging materials, poor temperature regulation, and relative humidity control. Because of the lack of an approved standard dosage for the application of various edible films/coatings, regulation and safety-related issues additionally hinder their use [ 107 ]. However, the use of phenolic compounds as carriers of active ingredients in the fabrication of edible films/coatings is a promising strategy.…”
Section: Application Of Phenolic Compounds In Packaging Films/coatingsmentioning
confidence: 99%